Climatic Influences of Deglacial Drainage Changes in Southern Canada at 10 to 8 ka Suggested by Pollen Evidence - Anderson, Thane; Lewis, C.F. (Géographie physique et Quaternaire, 1992)
ABSTRACTEnhanced meltwater discharge from proglacial lakes Agassiz and Barlow-Ojibway at about 9.6 to 8.3 ka BP. created cold localized climates over downstream water bodies, specifically Lake Minong and Mattawa phase lakes in the Great Lakes and Goldthwait Sea in the Gulf of St. Lawrence. The cooling effect of the meltwater drainage suppressed summer warming of the surface lake waters, reduced the growing season and thus altered the vegetation composition in the surrounding land areas. The vegetation responded in different ways as evidenced by five variants from the normal pollen succession.The pollen anomalies are most pronounced where the effect of increased meltwater discharge had a strong influence, such as within or along the margins of Lake Agassiz, Mattawa phase lakes, and the Goldthwait Sea, or in their lee areas, especially where these water bodies intersected ecotonal boundaries. Climatic effects were minimal or non-existent where the water surface areas were restricted such as the channelized drainage routes of the Ottawa and St. Lawrence rivers. Diversion of Lakes Agassiz and Barlow-Ojibway drainage to Hudson Bay after about 8.4 ka BP reinstated summer warming of the surface water in the Great Lakes-St. Lawrence system bringing the 9.6-8.3 ka cool period to a close.